1991
DOI: 10.1044/jshr.3406.1299
|View full text |Cite
|
Sign up to set email alerts
|

Social Interactions of Speech, and Language-Impaired Children

Abstract: Social interactions among preschool children were classified into four groups according to language ability: normally developing English, specific language impairment (SLI), speech impairment (SI), and English as a second language (ESL). The children were observed in naturalistic classroom interactions on three occasions. Conversational turns were coded according to initiations and responses, and addressee. The results reveal differences across the groups of children. Normal language peers initiate interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
132
0
11

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(148 citation statements)
references
References 15 publications
4
132
0
11
Order By: Relevance
“…These children also tended to exhibit different communicative behaviors from their peers who develop normally. In general, children with limited communication skills participated less often in peer interactions (Hadley & Rice, 1991;Rice, Sell, & Hadley, 1991). These children who initiated interactions less often than their peers who were developing normally (Conti-Ramsden & Friel-Patti, 1983) were more likely to initiate to adults and to shorten their responses or use nonverbal responses (Rice et al, 1991), and were less likely to respond to the initiation attempts of their peers (Hadley & Rice, 1991).…”
Section: Social Interactions Of Children With Special Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…These children also tended to exhibit different communicative behaviors from their peers who develop normally. In general, children with limited communication skills participated less often in peer interactions (Hadley & Rice, 1991;Rice, Sell, & Hadley, 1991). These children who initiated interactions less often than their peers who were developing normally (Conti-Ramsden & Friel-Patti, 1983) were more likely to initiate to adults and to shorten their responses or use nonverbal responses (Rice et al, 1991), and were less likely to respond to the initiation attempts of their peers (Hadley & Rice, 1991).…”
Section: Social Interactions Of Children With Special Needsmentioning
confidence: 99%
“…According to Hadley and Rice (1991), children with limited communication skills were less likely to receive responses to their initiations than were children with normal development. These researchers suggest that peers with normal development may have been less likely to respond to the initiations partially because of the limited intelligibility of some of the children who are speech delayed or the limited attention-getting abilities of these children.…”
Section: Social Interactions Of Children With Special Needsmentioning
confidence: 99%
“…Some studies indicate that children with language disorders tend to have poorer social skills, be withdrawn in social interactions, have less prosocial behavior and be less integrated into peer groups than children without language impairments. Furthermore, these children have been found to have fewer friends, be invited less frequently to take part in social activities and be liked less by others [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…Children with language problems seem to find it easier to communicate with adults, in particular with professionals, probably because they scaffold and give support in a systematic way. This has been shown in studies which have found that adults are preferred as conversational partners (Rice et al, 1991). However, the dependence on rich support from adults can also develop into a lack of interactional independence and turn into a constraining factor as the child becomes older.…”
Section: Peer Interaction In Children With Communication Problemsmentioning
confidence: 93%